Pengaruh Pemanfaatan Bungkil Inti Sawit Yang Difermentasi Menggunakan EM4 Sebagai Pakan Terhadap Rasio Konversi Pakan dan Pertumbuhan Ikan Gurami (Opshronemus gouramy) - Zakariyah, Akhmad; Kusdianto, Heru; Nikhlani, Andi; Ma’ruf, Mohamad; Wulandari, Retno (Universitas Batangahari Jambi, 2025)
A by-product of the palm oil business, palm kernel meal can be utilised as an alternate feed ingredient for cultured fish because of its really decent nutritional value. This research aimed to analyze the nutritional value of artificial feed with different EM4 concentrations in palm kernel cake fermentation and to analyze its effects on absolute weight growth, daily growth rate, specific growth rate, and feed conversion ratio. A Completely Randomized Design (CRD) with 3 treatments and 4 replications each was applied in this research. The treatments applied were unfermented palm kernel cake flour (P1), palm kernel cake fermented with 4 ml/kg concentration (P2), and palm kernel cake fermented with 8 ml/kg concentration (P3). The results of feed nutritional assesment showed that protein content of P1 (26.96%); P2 (38.51%); and P3 (38.71%); fat content in feed, P1 (6.62%); P2 (6.48%); and P3 (6.63%); Absolute weight growth P1 (0.78 g); P2 (1.18 g); and P3 (1.54 g); Daily growth rate, P1 (0.71%); P2 (1.10%); and P3 (1.31%); Total length growth, P1 (0.66 cm); P2 (0.74 cm); and P3 (0.99 cm); and Feed conversion ratio, P1 (3.28); P2 (2.34); and P3 (1.73). The results of the analysis of variance (ANOVA) at a 95% confidence level showed that different EM4 concentration treatments in palm kernel meal fermentation had a significant effect on growth, feed conversion ratio, and SGR (Specific Growth Rate) in Gourami Fish (Osphronemus gouramy).